2015
DOI: 10.1523/jneurosci.1217-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Distinct Population of Microglia Supports Adult Neurogenesis in the Subventricular Zone

Abstract: Microglia are involved in synaptic pruning both in development and in the mature CNS. In this study, we investigated whether microglia might further contribute to circuit plasticity by modulating neuronal recruitment from the neurogenic subventricular zone (SVZ) of the adult mouse striatum. We found that microglia residing in the SVZ and adjacent rostral migratory stream (RMS) comprise a morphologically and antigenically distinct phenotype of immune effectors. Whereas exhibiting characteristics of alternativel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
156
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 185 publications
(167 citation statements)
references
References 60 publications
8
156
2
1
Order By: Relevance
“…A subset of microglia was further shown to produce nitric oxide (NO), a signaling molecule that regulates the developmental switch from neuro- to astrogenesis and astroglial maturation (Peunova and Enikolopov, 1995; Béchade et al, 2011). Interestingly, apart from their effect on developmental neurogenesis, microglia can influence adult hippocampal neurogenesis by phagocytosis of apoptotic cells (Sierra et al, 2010) and are also able to provide trophic support to new adult born neurons in the hippocampus and SVZ (for review see Gemma and Bachstetter, 2013; Ribeiro Xavier et al, 2015). It is thus likely that the mechanisms microglia use to affect developmental neuro- and astrogenesis, can also be used to influence SVZ and hippocampal neurogenesis in the adult (Aarum et al, 2003; Kanski et al, 2014; Valero et al, 2016).…”
Section: The Crosstalk Between Microglia Neural Progenitors and Astrmentioning
confidence: 99%
“…A subset of microglia was further shown to produce nitric oxide (NO), a signaling molecule that regulates the developmental switch from neuro- to astrogenesis and astroglial maturation (Peunova and Enikolopov, 1995; Béchade et al, 2011). Interestingly, apart from their effect on developmental neurogenesis, microglia can influence adult hippocampal neurogenesis by phagocytosis of apoptotic cells (Sierra et al, 2010) and are also able to provide trophic support to new adult born neurons in the hippocampus and SVZ (for review see Gemma and Bachstetter, 2013; Ribeiro Xavier et al, 2015). It is thus likely that the mechanisms microglia use to affect developmental neuro- and astrogenesis, can also be used to influence SVZ and hippocampal neurogenesis in the adult (Aarum et al, 2003; Kanski et al, 2014; Valero et al, 2016).…”
Section: The Crosstalk Between Microglia Neural Progenitors and Astrmentioning
confidence: 99%
“…Specifically, it has been described that microglia at the SVZ and the rostral migratory stream, with features of alternatively activated microglia, seems to support both survival and migration of newly generated neuroblasts through the rostral migratory stream to the olfactory bulb. 48 In our experimental setting, endogenous CB2R activation might underlie the skewing of microglia toward a phenotype that fosters the migration of neuroblasts, an effect that deserves further studies.…”
Section: Discussionmentioning
confidence: 89%
“…Однако нельзя исключить, что и другие клетки могут способствовать этому промигрирующему эффекту in vivo. В частности, было описано, что микроглия в СВЗ и ростральном миграционном тракте с особенностями альтернативно активированной микроглии, по-видимо-му, поддерживает выживание и миграцию вновь образо-ванных нейробластов через ростральный миграционный тракт в обонятельную луковицу [48]. В наших экспери-ментальных условиях эндогенная активация CB2R может лежать в основе трансформации микроглии к фенотипу, способствующему миграции нейробластов, и этот вопрос заслуживает дальнейшего изучения.…”
Section: ■ обсуждениеunclassified
“…Recent data have established that mouse microglia possess a unique transcriptional and proteomic signature [20,21], including the unique expression of purinergic receptor P2Y12 [20,22] and transmembrane protein 119 [23] on the cell surface, now enabling specific labelling with antibodies. Evidence also indicates there are likely to be several heterogeneous subsets of microglia with region-specific functions, with a recent report highlighting a unique subset of fractalkine receptor (CX3CR1)-positive microglia present in the subventricular zone (SVZ), rostral migratory stream, and olfactory bulb that lacked ‘typical’ microglial markers Iba1, isolectin B4, and CD68, and appeared to be involved in the migration and integration of adult SVZ-derived neural progenitors into the olfactory bulb [24]. Other researchers have also used bone marrow chimeras and promoter-driven transgenic animals to label resident and infiltrating cells separately, and have found that in many conditions, the two subsets of cells vary considerably in their ability to phagocytose pathological deposits of protein, recruit other immune cells via antigen presentation, and contribute to pathology via production of neurotoxic substances [6].…”
Section: Contribution Of Myeloid Cells To Central Nervous System (mentioning
confidence: 99%
“…Therefore readers are strongly encouraged to evaluate the literature regarding neuro-inflammation and microglial activation with care, and to refrain from equating microglia and CNS macrophages in their own research. This can now be achieved relatively easily, as many reporter systems are available [10], and the transcriptional profiles of the two major subsets are well characterized [22,23,24,34]. Additionally, novel methods of depleting specific subsets of cells are under development [199], which may assist with the functional characterization of the heterogeneous subsets of microglia and other myeloid cells without confounding effects of irradiation on brain tissue, for example [200].…”
Section: From Bench To Bedside: Targets For Future Researchmentioning
confidence: 99%